PENGARUH PELATIHAN SUPERVISI TERHADAP KINERJA FIRST MANAGER PADA UNIVERSITAS X - Dewi Handayani Harahap (Jurnal Psikologi, 2016)
Ten first level managers in a university participated in this experimental research. They had problem related to the low capacity in completing their tasks. This problem has to be responded immediately since the university future highly depends on their shoulders. In order to build their work capacity, they were invited to participate in training. Their work performance data just before, after, and follow-up participating the training were compared. Therefore objective of this research is to determine the effectiveness of supervisory training on the performance of managers in a university. Using the performance scale, data research was collected. The repeated measure anova statistic design was used to find out the training effect on three stages i.e. before, after, and follow-up trainings. It was revealed that the F = 6.226 (p<.01). When comparing two stages using the paired sample t-test statistic design, it was revealed that the t pre-post = 2.722 (p<.05), t pre-follow up = 3.805 (p<.01), and t post-follow up = 2.00 (p>.05). The research conclusion was that the training had a significant effect on manager’s work performance. However, the effect might be temporarily since those managers’ participation is likely involuntarily. Besides that, the idea of this training came from the top management. Key words: supervisor, training, manager.